Comparison of Outcomes of Endoscopic Micro Discectomy Versus Conventional Discectomy for Lumber Disc Diseases. - Khan, Imran; Ali Noman, Muhammad; Rafi ullah, Rafi ullah; Khan, Zeeshan; Iqbal, Muhammad; Mukhtiar, Sajawal (Journal of Neonatal Surgery, 2025)
Introduction: Chronic lumbosacral pain is a communal and difficult clinical condition at the center of pain management. The most common surgical indication is back pain or intractable and severe functional impairment that does not respond to conservative measures. In this study we have compared the results of endoscopic d micro discectomy and conventional discectomy procedure. Material and Methods: This is six months study was conducted in the department of neurosurgery Hayatabad Medical Complex Peshawar from 1st Feb 2025 to 1 August 2025. We included 54 patients with severe lower back pain who did not improve after long-term conservative treatment and who had level 3 disc prolapse, radiating to one or both lower limbs. Oswestry Disability Index (For Low Back Pain) was documented with questionnaire comeback and applied as a clinical tool for valuation. Results: The average age of the 54 patients was 46 years and 75% of patients have paracentral disc protrusion. The mean endoscopic micro discectomy surgery time was 110 minutes; was longer than conventional discectomy (82 minutes). However, blood loss was very small compared to conventional discectomy. According to the ODI result, both conventional and endoscopic discectomy gave same outcomes in all classes. Conclusion: Endoscopic micro discectomy is a new, effective and safe procedure that reduces the invasiveness of the surgical approach. The results obtained by this approach are comparable with those obtained with open discectomy to alleviate symptoms during prolonged observation, and because the tissue has minimal trauma, it is much better in early mobilization and morbidity